Implementing strategies to manage wellbeing at work during the pandemic. - Gatsiopoulou, Eleni (2020)
Implementation of wellbeing strategies in the workplace is a common practice for organisations to prevent occupational health and safety hazards and support their employees. This qualitative study was conducted to examine whether organisations have implemented well-being strategies during the pandemic. For this reason, 11 employees who are working in organisations in Greece took part in semi structured interviews. From the data collection arose that only few organisations -mainly in private sector- have adopted well-being programmes. Additionally, the outcomes of the research revealed the main barriers for implementation of well-being programmes in the workplace and highlighted the biggest challenges that employees had to handle due to this pandemic. The fact that employees had to deal with many new challenges had an impact both on their psychology and productivity. The findings of the research indicate that organisations were not well-prepared for an unprecedented situation like this one and organizations in Greece act more reactively than proactively and as a result, employees’ work-life balance can be affected easily.